Shakey grounds [videorecording (DVD)] - Danks, Jonny; Slobotkin, Trace; Nelsen, Eric (Actor); Cannon, Ella, 1990-; Thiebaud, Kelly; Roberts, Eric, 1956-; Ziegler, Mackenzie, 2004- (Gravitas Ventures, 2023)
Shakey Grounds follows a troubled musician and his band as they navigate personal demons and a shot at redemption with a disgraced record executive. After several obstacles, they rise together, finding purpose in their music and each other.